Sphenopalatine ganglion stimulation: a comprehensive evaluation across diseases in randomized controlled trials - Qin, Lingli; Chen, Dian; Li, Xian; Gao, Yue; Xia, Wanying; Dai, Hanxi; Qiu, Linjie; Yang, Jinsheng; Zhang, Lu (Frontiers in Neurology, 2024)
Background Current literature extensively covers the use of sphenopalatine ganglion stimulation (SPGs) in treating a broad spectrum of medical conditions, such as allergic rhinitis, cluster headaches, and strokes. Nevertheless, a discernible gap in the systematic organization and analysis of these studies is evident. This paper aims to bridge this gap by conducting a comprehensive review and analysis of existing literature on SPGs across various medical conditions. Methods This study meticulously constructed a comprehensive database through systematic computerized searches conducted on PubMed, Embase, CNKI, Wanfang, VIP, and CBM up to May 2022. The inclusion criteria encompassed randomized controlled trials (RCTs) published in either Chinese or English, focusing on the therapeutic applications of SPGs for various medical conditions. Both qualitative and quantitative outcome indicators were considered eligible for inclusion. Results This comprehensive study reviewed 36 publications, comprising 10 high-quality, 23 medium-quality, and three low-quality articles. The study investigated various diseases, including allergic rhinitis (AR), ischemic strokes (IS), cluster headache (CH), primary trigeminal neuralgia (PTN), pediatric chronic secretory otitis (PCSO), refractory facial paralysis (RFP), chronic tension-type headache (CTTH), as well as the analysis of low-frequency sphenopalatine ganglion stimulation (LF-SPGs) in chronic cluster headache (CCH) and the impact of SPGs on Normal nasal cavity function (NNCF). SPGs demonstrate efficacy in the treatment of AR. Regarding the improvement of rhinoconjunctivitis quality of life questionnaire (RQLQ) scores, SPGs are considered the optimal intervention according to the SUCRA ranking. Concerning the improvement in Total Nasal Symptom Score (TNSS), Conventional Acupuncture Combined with Tradiational Chinese Medicine (CA-TCM) holds a significant advantage in the SUCRA ranking and is deemed the best intervention. In terms of increasing Effective Rate (ER), SPGs outperformed both conventional acupuncture (CA) and Western Medicine (WM; P < 0.05). In the context of SPGs treatment for IS, the results indicate a significant improvement in the 3-month outcomes, as evaluated by the modified Rankin Scale (mRS) in the context of Cerebral Cortical Infarction (CCI; P < 0.05). In the treatment of CH with SPGs, the treatment has been shown to have a statistically significant effect on the relief and disappearance of headaches (P < 0.05). The impact of SPGs on NNCF reveals statistically significant improvements (P < 0.05) in nasal airway resistance (NAR), nasal cavity volume (NCV), exhaled nitric oxide (eNO), substance P (SP), vasoactive intestinal peptide (VIP) and neuropeptide Y (NPY). SPGs treatments for PCSO, RFP, and CTTH, when compared to control groups, yielded statistically significant results (P < 0.05). Conclusion SPGs demonstrate significant effectiveness in the treatment of AR, IS, and CH. Effective management of CCH may require addressing both autonomic dysregulation and deeper neural pathways. However, additional high-quality research is essential to clarify its effects on NNCF, PTN, PCSO, RFP, and CTTH. Systematic Review Registration PROSPERO, identifier CRD42021252073, https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=312429.